Microbial Community Structure Is Most Strongly Associated With Geographical Distance and pH in Salt Lake Sediments - Santini, Talitha C.; Gramenz, Lucy; Southam, Gordon; Zammit, Carla (Frontiers in Microbiology, 2022)
Salt lakes are globally significant microbial habitats, hosting substantial novel microbial diversity and functional capacity. Extremes of salinity and pH both pose major challenges for survival of microbial life in terrestrial and aquatic environments, and are frequently cited as primary influences on microbial diversity across a wide variety of environments. However, few studies have attempted to identify spatial and geochemical contributions to microbial community composition, functional capacity, and environmental tolerances in salt lakes, limiting exploration of novel halophilic and halotolerant microbial species and their potential biotechnological applications. Here, we collected sediment samples from 16 salt lakes at pH values that ranged from pH 4 to 9, distributed across 48,000 km2 of the Archaean Yilgarn Craton in southwestern Australia to identify associations between environmental factors and microbial community composition, and used a high throughput culturing approach to identify the limits of salt and pH tolerance during iron and sulfur oxidation in these microbial communities. Geographical distance between lakes was the primary contributor to variation in microbial community composition, with pH identified as the most important geochemical contributor to variation in microbial community composition. Microbial community composition split into two clear groups by pH: Bacillota dominated microbial communities in acidic saline lakes, whereas Euryarchaeota dominated microbial communities in alkaline saline lakes. Iron oxidation was observed at salinities up to 160 g L-1 NaCl at pH values as low as pH 1.5, and sulfur oxidation was observed at salinities up to 160 g L-1 NaCl between pH values 2-10, more than doubling previously observed tolerances to NaCl salinity amongst cultivable iron and sulfur oxidisers at these extreme pH values. OTU level diversity in the salt lake microbial communities emerged as the major indicator of iron- and sulfur-oxidising capacity and environmental tolerances to extremes of pH and salinity. Overall, when bioprospecting for novel microbial functional capacity and environmental tolerances, our study supports sampling from remote, previously unexplored, and maximally distant locations, and prioritising for OTU level diversity rather than present geochemical conditions.